The Analysis of The Youth Political Perception of 2019 General Elections in Jayapura City - Terianus L. Safkaur (International Journal of Social Service and Research, 2022)
Community participation in politics is an important indicator in measuring whether a country is democratic or not. The higher level of community participation results in the transparency of democracy. However, towards the 2019 elections, the absent of people in giving their voice was dominant in Indonesia. The apathetic groups who decided not to vote in elections have a variety of reasons. One of the reason is the distrust of the electoral system. Refers to the 2019 elections in the city of Jayapura, there was a tendency for some young people not to vote. In fact, elections are an important instrument in selecting leaders through democratic mechanisms. The two main objectives to be achieved through this research are first to find out the perspective of young people to view the general election. This is related to the understanding of the election as well as their hopes for the election and their political references if they decide to vote or not vote (abstentions). Second, this study aims to examine the models of youth participation in the election. Furthermore, this research will contribute to the gap of knowledge and studies related to youth their participation in general election, especially in the city of Jayapura. The city of Jayapura will become an important place of this case study because it’s social and political dynamics in analyzing youth perceptions.